Improving taxi-out operations at city airports to reduce CO2 emissions. (August 2019) - Postorino, Maria Nadia; Mantecchini, Luca; Paganelli, Filippo
Abstract: City airports cause many environmental concerns on population living in their neighbourhood and several actions are often imposed to airport operators and other involved stakeholders in order to reduce impacts and improve the life quality of neighbouring inhabitants. While some solutions have been widely studied – e.g., green surface accessibility – some others, such as taxi-out procedures, have received less attention. However, taxi-out procedures, which are part of the Landing and Take-Off (LTO) cycle, generate a remarkable amount of the whole airport environmental impact, especially carbon emissions. The goal of this paper is to propose an element-by-element approach that could help stakeholders to adopt targeted solutions. Particularly, the airport activity contributing to the airport carbon impact is split into elementary segments in order to compute the environmental effects produced by each elementary source of pollution. The advantage of this approach is the identification of targeted actions on specific segments, which generates more positive effects for the several involved stakeholders. While the study focuses on taxi-out procedures, the proposed approach is general and can be applied widely to simulate other airport activities that contribute to the airport carbon impacts. Highlights: An element-by-element approach is proposed to identify airport taxi-out solutions for CO2 reduction. Relevant transport variables, technologies and procedures are identified. CO2 and fuel saved for each solution are estimated for a test case. The test case of Bologna airport shows satisfactory results. Airport operators may take advantages of the proposed approach to reduce airport CO2 emissions.